(untitled) (World Bulletin of Public Health, 2024)
Chronic rhinosinusitis with nasal polyps (CRSwNP) is a common disease of the upper respiratory tract that significantly worsens the quality of life of patients. According to the World Health Organization, rhinosinusitis affects up to 30% of the population in developed countries, with CPRS occurring in 5-10% of these cases. Polypoid rhinosinusitis is observed in 20-30% of patients with chronic rhinosinusitis. CRSwNP is an important clinical entity diagnosed by the presence of both subjective and objective evidence of chronic sinonasal inflammation. Symptoms include anterior or posterior rhinorrhea, nasal congestion, hyposmia and/or facial pressure or pain that last for greater than 12 weeks duration. Nasal polyps are inflammatory lesions that project into the nasal airway, are typically bilateral, and originate from the ethmoid sinus. Males are more likely to be affected than females but no specific genetic or environmental factors have been strongly linked to the development of this disorder to date. CRSwNP is frequently associated with asthma and allergic rhinitis but the cellular and molecular mechanisms that contribute to the clinical symptoms are not fully understood. Defects in the sinonasal epithelial cell barrier, increased exposure to pathogenic and colonized bacteria, and dysregulation of the host immune system are all thought to play prominent roles in disease pathogenesis.